Impact of hypothermia during craniosynostosis repair surgery (2016)
tIntroduction: Hypothermia is recognized as a risk factor for perioperative complications inpaediatric patients. High surgical risk procedures serve as a model of exposure to that riskfactor. In particular, surgical correction of craniosynostosis serves as a model for measuringthe impact of hypothermia.Objective: To assess hypothermia-related morbidity and mortality in paediatric patientstaken to craniosynostosis correction.Methodology: Historical cohort study of patients taken to craniosynostosis correction andexposed to hypothermia.Results: With prior approval of the Ethics Committee of the institution, 54 records wereincluded in the analysis. No statistically significant differences were found betweenhypothermia and its impact in terms of morbidity and mortality (death, major bleeding,massive haemorrhage massive transfusion, disseminated intravascular coagulation, needfor vasopressor support, mechanical ventilation time and length of stay, including admission to the intensive care unit). A clinically significant increase in bleeding (severe and massive) and severe hypothermia was found (28.6% vs. 40% and 14.3% vs. 40%, respectively). Conclusions: No statistical differences were found in terms of morbidity and mortality with severe hypothermia (and moderate/severe hypothermia).